(untitled) - Madlenak, Radovan (Doprava a spoje, 2005)
The design of a suitable system of postal technology is the most important issue for providing elementary functions of the postal enterprise. A correct technology decision depends on the chosen postal infrastructure model and specific optimization method and process. This article dealt with the choice of the suitable optimization method to find the optimum number and placement of the highest level nodes of the postal transportation network.